Enhancing surface integrity of medical Ti–6Al–4V alloy via magnetic field-assisted mass polishing - Rui Gao; Dawei Luo; Yee Man Loh; Chi Fai Cheung; Chen Jiang; Chunjin Wang (Journal of Materials Research and Technology)
The Ti–6Al–4V (TC4) alloy is extensively utilized in the medical industry. However, untreated TC4 alloy exhibits a high degree of roughness, significantly impeding its performance. Enhancing the polishing efficiency of TC4 has thus become a critical focus. This study investigates the feasibility of magnetic field-assisted mass polishing (MAMP) for medical TC4 alloy. A comprehensive series of experimental studies were conducted to evaluate and analyze the surface integrity before and after the polishing process. The empirical results demonstrate the effectiveness of the proposed method for mass polishing TC4 alloy. The polished samples achieved a minimum surface roughness (Sa) of 6.9 nm after 20 min of treatment, with a material removal rate (MRR) of 55.8 nm/min. Post-polishing, the mechanical properties and surface Post-polishing after MAMP, the TC4 samples do not exhibit any significant changes in elemental weight% or phase transformation when compared to the initial samples. Having a smaller surface roughness is advantageous for achieving a higher flexural strength and hardness and improving surface wettability showed slight improvement, with no significant chemical reactions or phase changes observed. This research provides pivotal insights and recommendations for the ultra-precision mass polishing of medical TC4 alloys, potentially offering an optimal solution for polishing various medical components. Furthermore, this study presents straightforward and practical advice that significantly contributes to the advancement of manufacturing processes for medical parts and surface finishing methods.